Decrypting Environmental Impact on Human Psychology in William Golding’s Lord of the Flies. - SEGUEDEME, ALEXIS HERGIE; DANSOU, Bertin Yelindo; BOSSOUN, koumabe (My University, 2022)
This research work sets out to highlight the influence exercised by the environment on human being’s psychology as shown in disguised in William Golding’s Lord of the Flies. Every human being no matter his/her race, sex, age, or social affiliation at a given moment of his/her life has been subjected to the influence of some particular elements uncontrollable by the intrinsic power to dominate on anything. This may seem innocuous for a being not hardened, but in reality, it shows the weakness of human essence regarding to external or internal stimulations. To those stimuli, the mind and the soul are highly impacted to the extents of an abrupt behavioral change.
Keywords: Environmental; Impact; Human psychology